Investigation on high-velocity impact performance of multi-layered alumina ceramic armors with polymeric interlayers. (October 2016) - Rashed, A; Yazdani, M; Babaluo, AA; Hajizadeh Parvin, P
In this study, ballistic behavior of multi-layered ceramic armors under high velocity impact is studied numerically. The model consists of 2D-axisymmetric Lagrangian approach with Johnson–Holmquist constitutive model for alumina ceramic tiles, Mie–Gruneisen equation of state for polymeric interlayers, and Johnson–Cook constitutive relation for Armor Piercing (AP) projectile. The finite element results obtained from various armor layups show the potentiality of multi-layered ceramic armor in extending conoid fracture through the ceramic layers, thus leading to the increase in the armor performance. It is illustrated that besides ceramic armor layup, interlayers of ceramic tiles have a significant role in increasing the armor performance. Finally, the effect of different polymeric interlayers on ballistic performance of multi-layered ceramic armors against AP projectile is investigated. In order to measure the ballistic performance of the armors, various criteria are introduced. Depth of penetration of the projectile in the armor, residual velocity of the projectile, time duration in which the projectile is engaged inside the armor, projectile tip erosion during impact, and interaction volume ratio are some of these criteria. The study indicates that armor layup with thin front ceramic tiles backed by thicker tiles shows better conoid fracture extension and often better ballistic performance. Furthermore, among the polymeric interlayers used between the ceramic tiles, polystyrene causes the best and nylon causes the worst ballistic performance in the armor.